Tissue-Sparing Posterior Cervical Fusion With Interfacet Cages: A Systematic Review of the Literature. Issue 2 (April 2020) - Laratta, Joseph L.; Gupta, Karishma; Smith, William D.
Study Design: Literature review. Objectives: Posterior cervical interfacet cages are an alternative to lateral mass fixation in patients undergoing cervical spine surgery. Recently, a percutaneous, tissue-sparing system for interfacet cage placement has been developed, however, there is limited clinical evidence supporting its widespread use. The aim was to review studies published on this system for patient reported outcomes, radiographic outcomes, intraoperative outcomes, and complications. Methods: Four electronic databases (PubMed, EMBASE, Scopus, and MEDLINE) were queried for original published studies that evaluated the percutaneous, tissue-sparing technique for posterior cervical fusion with interfacet cage placement. All studies reporting on open techniques and purely biomechanical studies were excluded. Results: The extensive literature search returned 7852 studies. After systematic review, a total of 7 studies met inclusion criteria. Studies were independently classified as retrospective or prospective cohort studies and each assessed by the GRADE criteria. Patient reported outcomes, radiographic outcomes, intraoperative outcomes, and complications were extracted from each study and presented. Conclusions: Tissue-sparing, posterior cervical fusion with interfacet cages may be considered a safe and effective surgical intervention in patients failing conservative management for cervical spondylotic disease. However, the quality of evidence in the literature is lacking, and controlled, comparative studies are needed for definitive assessment.